The Emerging Chondrocyte Channelome - Barrett-Jolley, Richard; Lewis, Rebecca; Fallman, Rebecca; Mobasheri, Ali (Frontiers in Physiology, 2010)
Chondrocytes are the resident cells of articular cartilage and are responsible for synthesising a range of collagenous and non-collagenous extracellular matrix macromolecules. Whilst chondrocytes exist at low densities in the tissue (1-10% of the total tissue volume in mature cartilage) they are extremely active cells and are capable of responding to a range of mechanical and biochemical stimuli. These responses are necessary for the maintenance of viable cartilage and may be compromised in inflammatory diseases such as arthritis. Although chondrocytes are non-excitable cells their plasma membrane contains a rich complement of ion channels. This diverse channelome appears to be every bit as complex as one might expect to find in excitable cells although in the case of chondrocytes their functions are far less well understood. The ion channels so far identified in chondrocytes include potassium channels (KATP, BK, Kv and SK), sodium channels (epithelial sodium channels, voltage activated sodium channels), transient receptor potential calcium or non-selective cation channels and chloride channels. In this review we describe this emerging channelome and discuss the possible functions of a range of chondrocyte ion channels.